2000
DOI: 10.1111/j.1559-1816.2000.tb02471.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Acceptance of Organizational Change: The Importance of Self‐Determination1

Abstract: Self‐determination theory (Deci & Ryan, 1985, 1987, 1991) proposes that internalization can be facilitated by supporting a person's autonomy. Autonomy support can be achieved using 3 means: giving a rationale for doing a task, offering some choice about how to do the task, and acknowledging feelings about the task. We examined the effects of these 3 factors on acceptance of change in a work organization. Employees from a large Canadian telecommunications company that was in the midst of profound transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(132 citation statements)
references
References 20 publications
3
117
0
3
Order By: Relevance
“…It also gives preliminary support to the premise that work-related events that have been shown to influence internalisation of work motivation (e.g., managerial support; Baard, Deci, & Ryan, 2004;Deci, Ryan, Gagné, Leone, Usunov, & Kornazheva, 2001;Gagné, Koestner, & Zuckerman, 2000) are likely to influence organisational commitment. It is interesting to note that the present results point to a distinction between the constructs of identified regulation and identification within commitment theories.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It also gives preliminary support to the premise that work-related events that have been shown to influence internalisation of work motivation (e.g., managerial support; Baard, Deci, & Ryan, 2004;Deci, Ryan, Gagné, Leone, Usunov, & Kornazheva, 2001;Gagné, Koestner, & Zuckerman, 2000) are likely to influence organisational commitment. It is interesting to note that the present results point to a distinction between the constructs of identified regulation and identification within commitment theories.…”
Section: Discussionmentioning
confidence: 81%
“…Future studies should also examine the role of social organisational context in promoting internalisation and commitment. Selfdetermination theory proposes that contexts that are "autonomy supportive" promote internalisation (Deci et al, 2001;Gagné et al, 2000). Future research should also examine how increases in commitment through internalisation are related to other organisational outcomes, such as absenteeism, turnover intentions, and in-role and extra-role performance-related behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Research on self-determination theory in the organizational context sheds some light on this question, having shown that supervisors play a vital role with respect to whether or not these needs are met (Gagné & Deci, 2005). More specifically, studies have found that supervisor autonomy support, defined as a constellation of manager behaviors that cultivate independence, openness, trust, and confidence among their employees, leads to greater fulfilment of the three core needs (Baard et al, 2004;Deci et al, 2001;Gagné, Koestner, & Zuckerman, 2000). To our knowledge, only one published study has focused on the relationship between supervisor autonomy support and burnout, and this was in a sample of high school athletic directors (Sullivan, Lonsdale, & Taylor, 2014).…”
mentioning
confidence: 90%
“…Furthermore, supervisor autonomy support has been shown to foster the fulfillment of these core needs (Baard et al, 2004;Deci et al, 2001;Gagné et al, 2000), thus helping to reduce staff burnout (Sullivan et al, 2014). It is important to recall, however, that only a small number of studies have been performed in samples of mental health providers, and these studies were restricted in scope.…”
mentioning
confidence: 99%
“…In the work context, employees who have supervisors with an autonomy supportive style report higher levels of satisfaction at work and better psychological health (Gillet et al 2013;Moreau and Mageau 2012), perform better (Baard et al 2004), and are more open to and accepting of organizational change (Gagné et al 2000) than those with supervisors with a controlling style. Other studies have shown that autonomy support predicts the satisfaction of workplace well-being through the satisfaction of intrinsic needs (Deci et al 2001).…”
Section: Contextual Factors and Employee Well-being: The Role Of Automentioning
confidence: 99%